Platelet-Derived Growth Factor-D Activates Complement System to Propagate Macrophage Polarization and Neovascularization - Xiong, Zhen; Wang, Qianqian; Li, Wanhong; Huang, Lijuan; Zhang, Jianing; Zhu, Juanhua; Xie, Bingbing; Wang, Shasha; Kuang, Haiqing; Lin, Xianchai; Lee, Chunsik; Kumar, Anil; et al. (Frontiers in Cell and Developmental Biology, 2021)
Platelet-derived growth factor-D (PDGF-D) is highly expressed in immune cells. However, the potential role of PDGF-D in immune system remains thus far unclear. Here, we reveal a novel function of PDGF-D in activating both classical and alternative complement pathways that markedly increase chemokine and cytokine responses to promote macrophage polarization. Pharmacological targeting of the complement C3a receptor using SB290157 alleviated PDGF-D-induced neuroinflammation by blocking macrophage polarization and inhibited pathological choroidal neovascularization. Our study thus suggests that therapeutic strategies targeting both PDGF-D and the complement system may open up new possibilities for the treatment of neovascular diseases.